Audio encryption and decryption using 3D AES block cipher algorithm / Nur Fattin Nadhrah Saifuddin - Saifuddin, Nur Fattin Nadhrah (2018)
Nowadays, people are usually send the data via Internet or thumb drive instead of using letter. Especially for audio data, people are not sending audio using letter but send it over the radio channel or internet devices in order to receiver can hear it well. Besides, how to keep the audio as a secret if people can send it and receive it very well? Audio encryption and decryption introduce the process where we can keep the data secret, only for sender and receiver can accept the message. The audio will be encrypt to unknown message and will be decrypt by receiver using secret key. This technique will be tested in order to compare with other research. This project purpose is to identify the implementation testing security using 3D AES block cipher algorithm. Besides, this encryption using audio as a data in order to design and develop the project. This project also measure the security analysis on linearity test. In other and, ADDIE model is a methodology that including analysis, design, development, implementation and evaluation that complete the cycle of the project that starts from get the title of project, survey and collect the information about encryption and decryption, and specify the scope to 3D AES block cipher algorithm.